ANALISIS ENERGY SECURITY BERDASARKAN RELIABILITY ENERGY TERHADAP PRODUKTIVITAS ENERGI PADA PABRIK PALM KERNEL OIL PT. PERKEBUNAN NUSANTARA V TANDUN, ROKAN HULU - Pujangga, Rama; Daulay, Iwan Nauli; ', Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the level of Energy Security based on Reliability Energy at the Palm Kernel Oil Mill PT. PTPN V Tandun, Rokan Hulu. By using Slovin formula, the number of samples taken in the amount of 66 respondents who are the employees of the factory. Data analysis method is used descriptive analysis. These results indicatethat the Energy Security based on Reliability Energy is quite reliable on Energy Productivity at the Palm Kernel Oil Mill PT. PTPN V Tandun, Rokan Hulu. From the research result the company should be further improvethe tendance, training, and development of biogas technology innovation to improve the reliability of the power usage of biogas and minimize diesel consumption.Keywords: Energy Security, Reliability Energy, and Energy Productivity